Microbial Fabrication of Nanomaterial and Its Role in Disintegration of Exopolymeric Matrices of Biofilm - Nag, Moupriya; Lahiri, Dibyajit; Sarkar, Tanmay; Ghosh, Sujay; Dey, Ankita; Edinur, Hisham Atan; Pati, Siddhartha; Ray, Rina Rani (Frontiers in Chemistry, 2021)
Bacterial biofilms are responsible for the development of various chronic wound-related and implant-mediated infections and confer protection to the pathogenic bacteria against antimicrobial drugs and host immune responses. Hence, biofilm-mediated chronic infections have created a tremendous burden upon healthcare systems worldwide. The development of biofilms upon the surface of medical implants has resulted in the failure of various implant-based surgeries and therapies. Although different conventional chemical and physical agents are used as antimicrobials, they fail to kill the sessile forms of bacterial pathogens due to the resistance exerted by the exopolysaccharide (EPS) matrices of the biofilm. One of the major techniques used in addressing such a problem is to directly check the biofilm formation by the use of novel antibiofilm materials, local drug delivery, and device-associated surface modifications, but the success of these techniques is still limited. The immense expansion in the field of nanoscience and nanotechnology has resulted in the development of novel nanomaterials as biocidal agents that can be either easily integrated within biomaterials to prevent the colonization of microbial cells or directly approach the pathogen overcoming the biofilm matrix. The antibiofilm efficacies of these nanomaterials are accomplished by the generation of oxidative stresses and through alterations of the genetic expressions. Microorganism-assisted synthesis of nanomaterials paved the path to success in such therapeutic approaches and is found to be more acceptable for its “greener” approach. Metallic nanoparticles functionalized with microbial enzymes, silver–platinum nanohybrids (AgPtNHs), bacterial nanowires, superparamagnetic iron oxide (Fe3O4), and nanoparticles synthesized by both magnetotactic and non-magnetotactic bacteria showed are some of the examples of such agents used to attack the EPS.